Reform and democracy in Mozambique, 1983-1991 - Morgan, Glenda Nadine (Rhodes University, Faculty of Humanities, Department of Political Studies, 1992)
Africa is currently experiencing a movement toward more democratic systems of government. The causes of such changes are numerous, but the literature on African democratization, like that on similar changes elsewhere in the world, places emphasis on the role of internal or domestic factors. The role of international pressures toward democratization is almost completely ignored. The case of Mozambique illustrates the dangers of such an omission. During the past decade Mozambique has undergone considerable political change. The single-party, Marxist-Leninist oriented state has been replaced by a multi-party system, devoid of explicit references to any guiding ideology. The government has also expanded its contacts with the West, particularly by means of its assuming membership of the International Monetary Fund and the World Bank. These changes in Mozambique's political orientation have been accompanied by economic reforms, designed to arrest the precipitous decline in the Mozambican economy. In this dissertation I argue that the causes of both the economic and political reforms lie in this decline and in the government's need to secure capital and debt relief internationally. In order to do this, the Mozambican government had to change the aspects of its political system which were seen as being unacceptable by the West, in particular the lack of multi-party competition and its overtly Marxist orientation and close ties to socialist countries. Because the reforms had their primary genesis in Mozambique's need for international acceptance and not in the growth of popularly based democratic organisations, the reforms are fragile and their meaningfulness questionable.
Keywords: Mozambique -- Politics and government -- 1975-1994; Mozambique -- Economic conditions -- 1975-